UTILIZAÇÃO DE PLANTAS DE BAMBU NO TRATAMENTO DE ESGOTO SANITÁRIO PELO SISTEMA DE ALAGADOS CONSTRUÍDOS - Quege, Karina Eliane; Almeida, Rogério de Araújo; Ucker, Fernando Ernesto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707440 This study aimed to evaluate the efficiency of three species of bamboo (Guadua angustifolia,Phyllostachys aurea and Phyllostachys bambusoides) in the sanitary sewage treatment, with avertically downward sub-surface flow constructed wetlands, in Goiânia, GO, Brazil. Sewage from auniversity was applied to asbestos cement water tanks with 1,000 liters volume capacity, filledwith oxisol above a 0.26 m drainage layer of gravel # 3. Bamboo seedlings were planted in ninetanks and three tanks remained without plants (controls). The wastewater was captured at theinitial part of a facultative pond and applied to the surface of the treatment tanks, three times aday, using a timer controlled pump. It was used a hydraulic retention time (HRT) of 2.3 days during150 days and a HRT of 5.2 days for 360 days. Inside the treatment tanks, the wastewater wasmaintained two inches below the substrate surface. For a period of twelve months sewagesamples were collected before and after passing through each treatment tank. The samples weresubmitted to laboratory testing for determination of chemical oxygen demand, biochemicaloxygen demand, ammonia nitrogen and phosphates. The evapotranspiration rate of eachtreatment was measured, their efficiencies in removing the sewage pollutant load were calculatedand the behavior of plants in treatment tanks were observed. The results were submitted to F andTukey (5% of probability) tests. In general, the specie G. angustifolia showed greater efficiency inremoving the pollution load of all attributes. There was a higher removal of BOD and phosphate atHRT of 5.2 days. The HRT of 2.3 days was better on removing ammonia nitrogen.